(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Climate change significantly impacts socio-economic activities in Vietnam’s Mekong Delta, especially agriculture and tourism. Agritourism offers a path for local economic development and climate adaptation. This study assesses agritourism development in the Mekong Delta and proposes climate adaptation solutions, based on surveys and expert interviews. Findings reveal the region’s rich natural conditions and unique culture offer considerable agritourism potential. However, it faces challenges from climate change, including sea-level rise, saltwater intrusion, and drought. Proposed solutions involve sustainable agricultural models, green technologies, enhanced community awareness, and supportive policies. These aim to mitigate climate impacts, foster sustainable agritourism, and contribute to regional livelihoods and environmental protection.